1998
DOI: 10.1163/156855598x00026
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free anionic polymerization of methyl methacrylate

Abstract: Abstract�Results on the metal-free anionic polymerization of methyl methacrylate (MMA) are presented. MMA was polymerized in tetrahydrofuran, using tetrabutylammonium diethyl 2-ethylmalonate and tetrabutylammonium 2-nitropropanate as initiators. Immediate polymerization was observed only in cases where the initators did not contain traces of their precursor molecules, the presence of which causes an appreciable inhibition period. This is attributed to the transfer reaction between active species and the precur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
3
12
0
Order By: Relevance
“…Bidinger and Quirk 32) used TBA + 9-methylfluorenide at low concentration as an initiator for the polymerization of MMA at ambient temperature resulting in polymers with rather broad MWD. Bandermann et al 33) also reported induction periods and broad MWD's as well as the presence of residual initiator in MMA polymerization using TBA malonate as initiator. They also found evidence for Hofmann elimination as a termination reaction.…”
Section: Introductionmentioning
confidence: 94%
“…Bidinger and Quirk 32) used TBA + 9-methylfluorenide at low concentration as an initiator for the polymerization of MMA at ambient temperature resulting in polymers with rather broad MWD. Bandermann et al 33) also reported induction periods and broad MWD's as well as the presence of residual initiator in MMA polymerization using TBA malonate as initiator. They also found evidence for Hofmann elimination as a termination reaction.…”
Section: Introductionmentioning
confidence: 94%
“…In the metalfree anionic polymerization of methyl methacrylate (MMA) initiated by tetrabutylammonium diethyl ethyl malonate in THF (obtained from the reaction of tetrabutylammonium hydroxide with diethyl ethyl malonate), Fieberg et al [14] also reported very long induction periods similar to those shown in Figure 1 and 2. It was concluded that the more nucleophilic oligo-MMA anion reacts with unreacted initiator precursor, diethyl ethyl malonate.…”
Section: Similar Transfer Reactions In Other Polymerizationsmentioning
confidence: 88%
“…A similar behavior has also been observed in some other anionic and group transfer polymerizations. [14,15] Therefore, the explanation and kinetic analysis of this phenomenon is also included in this communication.…”
Section: Introductionmentioning
confidence: 99%
“…Bidinger and Quirk 3) used TBA + 9-methylfluorenide as initiator for the polymerization of MMA, obtaining PMMA with broad MWDs. Bandermann et al 4) also reported broad MWDs, residual initiator and Hoffmann elimination as termination reaction when using TBA + malonate as initiator. Baskaran et al 5) reported similar results and explained these observations by a reversible initiation step when using initiators with low pK a values like malonates and fluorenides.…”
Section: Introductionmentioning
confidence: 96%